Antara Kekayaan dan Kesederhanaan Dalam Perspektif Filsafat Ekonomi Islam: Peran Harta Pada Pembentukan Karakter Pendidikan Islam - Ahmad Wahyudi Zein; Maura Faradita; Mhd Khairul Anhar Nasution; Yeni Yolanda Simatupang (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Experts say that human fundamentals, including the role of the economy, must form the foundation of educational philosophy and practice. Education is both a human need and a symptom. In the sense that without education, a person cannot be considered a true human being and cannot carry out their role as a valuable human being in their daily life. Creating a flawless Muslim human being in the sense of al-insan al-kamil—that is, a person who is constantly istiqomah and continuously proficient in using their bodily and spiritual abilities to always submit to and obey Allah SWT—is the ultimate goal of the Essence of Humanity program in Islamic education.